Eficacia y residualidad del Pyriproxifen sobre el Aedes aegypti y la susceptibilidad del vector frente al larvicida en Mazan Y Nauta, Loreto – Perú - Flores del Aguila, Rosa Victoria (2025)
The objective of this study was to evaluate the efficacy and residual activity of Pyriproxifen on third-stage Aedes aegypti larvae and to determine susceptibility to this larvicide in Mazan and Nauta strains, along with their Rockefeller control strains. Tests were conducted in the laboratory at a concentration of 0.01 ppm. Efficacy was assessed by inhibition of emergence (EI) at 24 hours and residual activity for 90 days by monthly exposure of new larvae without renewing the solution. Susceptibility was determined based on the EI percentage, with strains with 98–100% EI considered susceptible. The results demonstrated 100% EI efficacy at 24 hours in all three strains (Mazan, Nauta, and Rockefeller). With 100% residual EI activity up to 30 days, decreasing to 89% in Mazan and 86.2% in Nauta at 60 days, and reducing to 19.3% and 52%, respectively, at 90 days. The three strains tested were susceptible to pyriproxyfen, with emergence inhibition of 100%, 98.7%, and 100%, respectively. Statistical analysis (ANOVA and Tukey's post hoc test (p=0.05)) showed no significant differences between the strains tested. It is concluded that pyriproxyfen is effective, with an effective residual activity of up to 60 days in the Mazan and Nauta strains; and they remain susceptible. These findings support its use in vector control programs in endemic areas of the Peruvian Amazon.